Legal research and writing for paralegals - Bouchoux, Deborah E., 1950- (New York : Wolters Kluwer, 2017)
Legal Research and Writing for Paralegals emphasizes the issues that paralegals encounter in practice. Thoroughly up to date, the Eighth Edition continues to combine crisp text with visual aids, writing samples, tips, and pointers. Designed specifically for paralegal students, the author's classroom-tested approach teaches cutting-edge research skills, writing style, and proper citation form - to equip students with an essential skill set and well-founded confidence. Popular with students and respected by instructors, Legal Research and Writing for Paralegals, features: An integrated approach that consistently connects writing strategies and research ; Timely and detailed coverage of electronic research, including Internet research and fee-based services such as Lexis and Westlaw ; Pointers throughout for using electronic resources effectively ; Helpful charts and diagrams that clearly illustrate complex topics ; Practice tips in each chapter that offer useful suggestions for workplace success ; Internet Assignments - which can be made state-specific - that give you practice finding information on-line ; Step-by-step guidance for proper citation form ; Legal writing samples, such as letters, a court brief, and a legal memorandum. Thoroughly updated, the Eighth Edition includes: Entirely new assignments in every chapter ; Updates to the United States code ; GovInfo offering free, official, and authenticated documents from all three branches of government ; New research sources, such as the Law Review Commons, for free access to thousands of law review articles ; Revamped and updated discussion of citation formCiting Internet sources ; Citation software and automatic citation tools, such as Lexis for Microsoft Office, Thomson Reuters's Drafting Assistant, Zotero, and Juris-M ; The new platforms for Lexis Advance and WEstlaw, with accompanying assignments ; Ravel Law, the newest entrant into computer-assisted legal research ; Research management tools Zotero, Juris-M and Evernot. -- From back cover.
Finding the law -- The federal and state court systems -- Statutory law -- Case law and judicial opinions -- The use of digests, annotated law reports, and words and phrases -- Encyclopedias, periodicals, treatises, and restatements -- Miscellaneous secondary authorities -- Legal citation form -- Updating and validating your research -- Special research issues -- The digital library : Lexis advance, Westlaw, and nonprint research sources -- E-Research : legal research using the Internet -- Overview of the research process -- Back to basics -- Strategies for effective writing -- Legal correspondence -- Legal memoranda -- Legal briefs -- Postwriting steps.
Includes bibliographical references and index.
Keywords: Legal research -- United States; Legal composition; Legal assistants -- United States -- Handbooks, manuals, etc; Legal assistants; Legal composition; Legal research; United States; Handbooks and manuals